2018
DOI: 10.1038/s41467-018-02951-4
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin5 contributes to colorectal carcinogenesis by enhancing glutaminolysis in a deglutarylation-dependent manner

Abstract: Reversible post-translational modifications represent a mechanism to control tumor metabolism. Here we show that mitochondrial Sirtuin5 (SIRT5), which mediates lysine desuccinylation, deglutarylation, and demalonylation, plays a role in colorectal cancer (CRC) glutamine metabolic rewiring. Metabolic profiling identifies that deletion of SIRT5 causes a marked decrease in 13C-glutamine incorporation into tricarboxylic-acid (TCA) cycle intermediates and glutamine-derived non-essential amino acids. This reduces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 48 publications
7
116
0
2
Order By: Relevance
“…While being relatively important in normal cells, this process is essential for cancer cells, highlighting a potential tumor-specific metabolic target. Furthermore, the main target of SIRT5 is glutamate dehydrogenase 1 (GLUD1), which is also an important regulator of redox homeostasis; this is consistent with the previously described protective effect of SIRT5 against cellular oxidative stress [54]. Li et al found that Glutaminase 1 (GLS1), both the known isoforms, kidney-type glutaminase (KGA) and glutaminase C (GAC), is highly expressed in HCC, and that targeting GLS1 reduces the expression of stemness-related genes and cancer stem cells properties in vitro.…”
Section: Metabolic Enzymes and Cancersupporting
confidence: 87%
See 1 more Smart Citation
“…While being relatively important in normal cells, this process is essential for cancer cells, highlighting a potential tumor-specific metabolic target. Furthermore, the main target of SIRT5 is glutamate dehydrogenase 1 (GLUD1), which is also an important regulator of redox homeostasis; this is consistent with the previously described protective effect of SIRT5 against cellular oxidative stress [54]. Li et al found that Glutaminase 1 (GLS1), both the known isoforms, kidney-type glutaminase (KGA) and glutaminase C (GAC), is highly expressed in HCC, and that targeting GLS1 reduces the expression of stemness-related genes and cancer stem cells properties in vitro.…”
Section: Metabolic Enzymes and Cancersupporting
confidence: 87%
“…Antioxidant enzyme with mitochondrial localization, member of the thioredoxin system BC [111] HCC [112] MESO [113] EC [114] PC [115] SIRT1 NAD + -dependent protein deacetylase, plays key roles in DNA damage response and metabolic adaptation to energy stress. Along with PGC1α, is involved in chemotherapy-induced shift to OXPHOS in CRC cells CRC [47,116] SIRT5 NAD-dependent protein lysine demalonylase, desuccinylase and deglutarylase able to remove malonyl, succinyl, and glutaryl groups from the lysine residues of proteins CRC [54] Hexokinase II (HK2)…”
Section: Function Tumor Type Referencesmentioning
confidence: 99%
“…SIRT5 has been reported to possess dual roles in the regulation of various types of carcinoma, suggesting that SIRT5 acts as a tumor suppressor in hepatic cancer by inhibiting acyl-CoA oxidase 1 (42). However, SIRT5 has also been demonstrated to function as an oncogene in the carcinogenesis of colorectal cancer (CRC), potentially by stimulating glutamine metabolism through the activation of dehydrogenase 1 during the tricarboxylic-acid cycle in CRC cells (43). The fact that SIRT5 exhibits dual effects on the regression of different tumors may depend on the dominant factor in the microenvironment and the signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT5 was overexpressed in non-small cell lung cancer and colorectal cancer, high SIRT5 expression was an unfavorable predictor of survival. Overexpression of SIRT5 promoted cancer cell growth and drug resistance (34,35). SIRT5 was recently reported to be down-regulated in glioblastoma and its down-regulation was associated with poor prognosis (35,36).…”
Section: Discussionmentioning
confidence: 99%